ANALISIS DETERMINASI INFLASI DI INDONESIA - Ginting, Ari Mulianta (LPPM Universitas Terbuka, 2016)
Inflation is one of the macroeconomic indicators of concern for the government. The high inflation rate could disrupt the economy. This study tried to analyze the factors that cause inflation in Indonesia. This study used a qualitative and quantitative approach using secondary data period 2004-2014. The results of the qualitative analysis showed that in the period 204-2014 inflation rate in Indonesia was fluctuated  While the results of the regression analysis VECM, indicating that the inflation rate in Indonesia is influenced by the variable of  exchange rate, money supply and level of consumption. While the GDP variable has a negative influence on inflation. In order to control the inflation rate the government could use macroeconomic variables such as exchange rates, the money supply well. Besides controlling public consumption at a good level and increase the production of goods and services to meet community needs. Inflasi merupakan salah satu indikator ekonomi makro perhatian bagi pemerintah. Tingkat inflasi yang tinggi dapat mengganggu perekonomian. Penelitian ini mencoba untuk menganalisis faktor-faktor yang menyebabkan inflasi di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dan kuantitatif dengan menggunakan periode data sekunder 2004-2014. Hasil analisis kualitatif menunjukkan bahwa tingkat inflasi periode 204-2014 di Indonesia berfluktuasi. Sementara hasil VECM menunjukkan bahwa tingkat inflasi di Indonesia dipengaruhi oleh variabel nilai tukar, uang beredar dan tingkat konsumsi. Sementara itu variabel GDP memiliki pengaruh negatif pada inflasi. Untuk mengendalikan tingkat inflasi pemerintah dapat menggunakan variabel ekonomi makro seperti nilai tukar, uang memasok baik. Selain mengendalikan konsumsi masyarakat pada tingkat yang baik dan meningkatkan produksi barang dan jasa untuk memenuhi kebutuhan masyarakat.